Resident and elicited murine macrophages differ in expression of their glycomes and glycan-binding proteins. Issue 4 (15th April 2021) - Park, Diane D.; Chen, Jiaxuan; Kudelka, Matthew R.; Jia, Nan; Haller, Carolyn A.; Kosaraju, Revanth; Premji, Alykhan M.; Galizzi, Melina; Nairn, Alison V.; Moremen, Kelley W.; Cummings, Richard D.; Chaikof, Elliot L.
Summary: The pleiotropic functions of macrophages in immune defense, tissue repair, and maintenance of tissue homeostasis are supported by the heterogeneity in macrophage sub-populations that differ both in ontogeny and polarization. Although glycans and glycan-binding proteins (GBPs) are integral to macrophage function and may contribute to macrophage diversity, little is known about the factors governing their expression. Here, we provide a resource for characterizing the N-/O-glycomes of various murine peritoneal macrophage sub-populations, demonstrating that glycosylation primarily reflects developmental origin and, to a lesser degree, cellular polarization. Furthermore, comparative analysis of GBP-coding genes in resident and elicited macrophages indicated that GBP expression is consistent with specialized macrophage functions and correlates with specific types of displayed glycans. An integrated, semi-quantitative approach was used to confirm distinct expression patterns of glycans and their binding proteins across different macrophages. The data suggest that regulation of glycan-protein complexes may be central to macrophage residence and recruitment. Graphical abstract: Highlights: Glycan alterations distinguish macrophage populations primarily by lineage Resident macrophages exhibit a less heterogeneous glycan profile than elicited cells C-Type lectins are downregulated in elicited macrophages Siglec expression is correlated with prevalent sialyltransferase expression Abstract : Park et al. combines native glycan staining, metabolic tagging, structural glycomics, and transcript analysis to generate a map of glycan and glycan-binding protein expression in primary murine peritoneal macrophage sub-populations. The study serves as a resource to identify distinct molecular differences in macrophages according to cellular ontogeny and polarization.